Starch Nanoparticles for Food Packaging Applications: A Review - Sri Agustina (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
Starch is one of the most used biodegradable polymers for food packaging applications. It has suitable properties and characteristic in the development of sustainable materials, including the biodegradability, non-toxicity, affordability, natural abundance, and renewability. The development of starch materials in form of nanoparticles has become more attractive due to its capability to functionalize with bioactive compound in forming of functional packaging materials. It also can be used as nanofillers to enhance the mechanical and barrier properties of biocomposite materials for food packaging materials. This article provides a short review of the development starch-based nanoparticles for food packaging applications.